Hardy’s Sue and her failure in the mirror of foucauldian concept of individuality - Pedram Lalbakhsh,; Nasser Maleki,; Nahid Jamshidi Rad, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The paper is a study of Thomas Hardy’s female character, Sue, in Jude the Obscure. To discover the reasons for Sue’s failure in dealing with both society and her personal life, the character is analyzed from the framework of Foucauldian power relations and the concept of individuality. According to Foucault’s dynamic view of power relations, individuals or subjects in every society are free and dynamic and power produces individuals who act, and are not simply objects upon whom others act. Individuals change and take shape after they engage in power relations, and this is how our participation in power relations literally makes us who we are. In other words, an individual is not passive and a victim of power relations, but free to succumb to the demands of power relations or use the possibilities before him and practise his own ethics. To Foucault, subjects can practise their individual freedom through ‘care of the self’; that is, one can achieve a self other than what power relations impose. Considering Foucault’s ideas in this regard the authors of this paper argue that while the female protagonist of Hardy’s novel enjoys all three Foucauldian necessary elements for creating a new self other than the normalized self that power relation has created for her, what she creates as her new self is only a shadow, and a fading illusion. Her bitter defeat at the end is the proof of her illusive self and demonstrates that she has been unable to shake her normalized self off. When looked from a Foucauldian point of view she is a failure – still a normalized self masked under the figure of a new self.